Effect of intranasal stem cell administration on the nigrostriatal system in a mouse model of Parkinson's disease - Salama, Mohamed; Sobh, Mahmoud; Emam, Mahmoud; Abdalla, Ahmed; Sabry, Dina; El Gamal, Mohamed; Lotfy, Ahmed; El Husseiny, Mahmoud; Sobh, Mohamed; Sahalash, Ali; Mohamed, Wael Mohamed Yousef (Spandidos Publications, 2017)
Parkinson's disease (PD) is the second most common neurodegenerative disease worldwide. It affects the locomotor system, leading to a final severe disability through degeneration of dopaminergic neurons. Despite several therapeutic approaches used, no treatment has been proven to be effective; however, cell therapy may be a promising therapeutic method. In addition, the use of the intranasal (IN) route has been advocated for delivering various therapies to the brain. In the present study, the IN route was used for administration of mesenchymal stem cells (MSCs) in a mouse model of PD, with the aim to evaluate IN delivery as an alternative route for cell based therapy administration in PD. The PD model was developed in C57BL/6 mice using intraperitoneal rotenone administration for 60 consecutive days. MSCs were isolated from the mononuclear cell fraction of pooled bone marrow from C57BL/6 mice and incubated with micrometer‑sized iron oxide (MPIO) particles. For IN administration, we used a 20 µl of 5x105 cell suspension. Neurobehavioral assessment of the mice was performed, and after sacrifice, brain sections were stained with Prussian blue to detect the MPIO‑labeled MSCs. In addition, immunohistochemical evaluation was conducted to detect tyrosine hydroxylase (TH) antibodies in the corpus striatum and dopaminergic neurons in the substantia nigra pars compacta (SNpc). The neurobehavioral assessment revealed progressive deterioration in the locomotor functions of the rotenone group, which was improved following MSC administration. Histopathological evaluation of brain sections in the rotenone+MSC group revealed successful delivery of MSCs, evidenced by positive Prussian blue staining. Furthermore, rotenone treatment led to significant decrease in dopaminergic neuron number in SNpc, as well as similar decrease in the corpus striatum fiber density. By contrast, in animals receiving IN administration of MSCs, the degeneration caused by rotenone treatment was significantly counteracted. In conclusion, the present study validated that IN delivery of MSCs may be a potential safe, easy and cheap alternative route for stem cell treatment in neurodegenerative disorders